Compressive properties of hollow lattice truss reinforced honeycombs (Honeytubes) by additive manufacturing: Patterning and tube alignment effects. (15th October 2018) - Xu, Jun; Wu, Yaobo; Wang, Lubing; Li, Jiani; Yang, Yuwei; Tian, Yuli; Gong, Zizheng; Zhang, Pinliang; Nutt, Steven; Yin, Sha
Abstract: Honeytubes, a novel type of honeycomb formed by reinforcement with lattice trusses, were reported to exhibit enhanced buckling resistance. However, an in-depth analysis for the compressive performance and energy absorption capacity was lacking. In this paper, the effects of microstructure and tube alignment on compressive properties were studied. Four types of honeytubes were designed based on different topologies, geometries and tube patterns, and fabricated by selective laser sintering (SLS). Out-of-plane compression tests and finite element simulation were performed for the analysis. Results indicated that incorporation of lattice in honeycombs resulted in greater local strain in tubes and tube-rib connections. However, honeytubes exhibited superior energy absorption capability, even surpassing that of some metallic lattices. Balancing the configuration of tubes in honeytubes could ensure enhanced mechanical performance. This work demonstrates that materials designed by capitalizing on micro-topologies can regulate mechanical properties and provide insights for guiding the development of new materials. Graphical abstract: Highlights: Hollow lattice truss reinforced honeycombs (honeytubes) were designed and printed. Compressive properties can be manipulated by capitalizing on micro-topologies. Honeytubes exhibited superior energy absorption capability over honeycombs. Balanced tube patterns can ensure enhanced compressive performance of honeytubes.